การขยายขอบเขตงานของผู้สื่อข่าวสตรีในวิชาชีพวารสารศาสตร์ - วีณา แก้วประดับ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this research is to study the work expansion of female reporter in terms of the work types and positions. The study also aims to find out what factors are supported or Emitted the expansion of news work for female reporters. This research surveyed 385 female reporters from 20 media organizations and conducted depth interview with 10 senior female reporters and 13 media executives working in various news media organizations. The findings show that: Female reporters have highly news career expansion in terms of the numbers of personel and the variety of news types and media organizations. The promotion of females’ news positions from reporter to executive are rare. Some female reporters have been promoted to low and medium level but not to high executive level. For the factors concerning with media work expansion, female’s her own ability and potency are the most important factor. Female’s personalities, feminities, woman rights, colleagues and bosses, including media organizational policy are the next important factors, respectively. On the other hand, various family factors are the most inhibited in news work expansion of female reporter, including the nature of journalism career itself.